The very busy spider - Carle, Eric. (New York : Philomel Books, 1984)
The farm animals try to divert a busy little spider from spinning her web, but she persists and produces a thing of both beauty and usefulness. The pictures may be felt as well as seen.
130
Accelerated Reader AR
Keywords: Spiders -- Juvenile fiction; Spider webs -- Juvenile fiction; Domestic animals -- Juvenile fiction; Toy and movable books